Pets, Death, and Taxes: Review of Barbara Ambros, Bones of Contention: Animal and Religion in Contemporary Japan - Marran, Christine (Humanimalia, 2013)
Barbara Ambros. Bones of Contention: Animal and Religion in Contemporary Japan. Honolulu: University of Hawaii Press, 2012. 265 pp. $55.00 (hb); $29.00 pb.